Type 2A and 2M von Willebrand Disease: Differences in Phenotypic Parameters According to the Affected Domain by Disease-Causing Variants and Assessment of Pathophysiological Mechanisms - Woods, Adriana Inés (2021)
Type 2A and 2M von Willebrand disease (VWD) broadly show similar phenotypic parameters, but involve different pathophysiological mechanisms. This report presents the clinical and laboratory profiles of type 2A and type 2M patients genotypically diagnosed at one large center. Higher bleeding score values and a higher incidence of major bleeding episodes were observed in type 2A compared with type 2M, potentially reflective of the absence of large and intermediate von Willebrand factor (VWF) multimers in 2A. In type 2A, most of disease-causing variants (DCVs) appeared to be responsible for increased VWF clearance and DCV clustered in the VWF-A1 domain resulted in more severe clinical profiles. In type 2M, DCV in the VWF-A1 domain showed different laboratory patterns, related to either reduced synthesis or shortened VWF survival, and DCV in the VWF-A2 domain showed patterns related mainly to shortened survival. VWF-type 1 collagen binding/Ag (C1B/Ag) showed different patterns according to DCV location: in type 2A VWD, C1B/Ag was much lower when DCVs were located in the VWF-A2 domain. In type 2M with DCV in the VWF-A1domain, C1B/Ag was normal, but with DCV in the VWF-A2 domain, C1B/Ag was low. The higher frequency of major bleeding in VWD 2M patients with DCV in the VWF-A2 domain than that with DCV in the VWF-A1 domain could be a summative effect of abnormal C1B/Ag, on top of the reduced VWF-GPIb binding. In silico modeling suggests that DCV impairing the VWF-A2 domain somehow modulates collagen binding to the VWF-A3 domain. Concomitant normal FVIII:C/Ag and VWFpp/Ag, mainly in type 2M VWD, suggest that other nonidentified pathophysiological mechanisms, neither related to synthesis/retention nor survival of VWF, would be responsible for the presenting phenotype.